Analisis Faktor Non-Keuangan terhadap Kinerja Bank Syariah di Indonesia - Hendrieta Ferieka; Irmatul Hasanah; Rezky Mehta Setiadi; Nur Falih Anwar (LPPM UBP, 2026)
This research analyzes non-financial aspects that influence the performance of Islamic banking in Indonesia, a sector that plays a crucial role in the country's financial stability and socio-economic welfare. Islamic banking in Indonesia has shown significant growth, reaching a market share of 10.41% in June 2022. Nevertheless, this sector faces challenges such as declining profitability and an increase in non-performing financing (NPF). Traditionally, bank performance evaluation has been based on financial statements. However, this study emphasizes the importance of non-financial performance indicators. Key non-financial factors identified and examined include Sharia Accounting Knowledge, Sharia Compliance, Ethical Values, Tax Relief, Sharia CSR Disclosure, and Service Quality. Through careful analysis, key findings indicate that Sharia Accounting Knowledge and Tax Relief have a significant impact on the performance of Islamic banking in Indonesia. These results underscore the need for a comprehensive approach in evaluating and improving Islamic banking performance, which not only considers financial metrics but also integrates crucial non-financial factors for the future growth and stability of the industry.